2015
DOI: 10.1002/art.39238
|View full text |Cite
|
Sign up to set email alerts
|

Determining Pathways to Improvements in Fatigue in Rheumatoid Arthritis: Results From the British Society for Rheumatology Biologics Register for Rheumatoid Arthritis

Abstract: Objective There is debate as to the role of inflammatory disease activity in the etiology of rheumatoid arthritis (RA)–related fatigue. We undertook this study to determine the relationship of fatigue to disease activity by examining pathways associated with change in fatigue in subjects starting anti–tumor necrosis factor (anti‐TNF) therapy for the first time. Methods Participants who had been recruited to the British Society for Rheumatology Biologics Register for RA provided information on fatigue (Short Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 45 publications
2
49
0
5
Order By: Relevance
“…Self-reported fatigue and poor mental health scores are associated with worse pain and greater central sensitisation in people with RA [38,39]. DAS28-ESR was significantly associated with fatigue and mental health in each study group.…”
Section: 104mentioning
confidence: 86%
“…Self-reported fatigue and poor mental health scores are associated with worse pain and greater central sensitisation in people with RA [38,39]. DAS28-ESR was significantly associated with fatigue and mental health in each study group.…”
Section: 104mentioning
confidence: 86%
“…Although there is evidence that fatigue responds in the short term to interventions that target inflammatory mediators of disease (4,5), there is a paucity of evidence supporting such associations in the long term (1,6).…”
Section: Introductionmentioning
confidence: 99%
“…To more specifically investigate the possible mechanisms of fatigue change, path analysis was undertaken and showed that improvements in fatigue are mediated by reductions in pain, rather than caused directly by changes in inflammatory disease activity (6). This result implies a need to target pain more specifically to improve fatigue management in the future, but pain has a complicated etiology (7), and while anti-TNF therapies are known to reduce pain caused by peripheral inflammation, evidence increasingly shows that they may modify central pain mechanisms in the central nervous system (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The direction of the association, thus is depression induced by fatigue or fatigue induced by depression, is under debate. According to Druce et al, both directions are possible [39]. A dynamic conceptual model of RA fatigue showed the bi-directional relation for depression and fatigue [40].…”
Section: Discussionmentioning
confidence: 99%